39 Development of a nomogram to predict interval debulking surgery feasibility when primary cytoreduction is not an option. (13th November 2020) - Rosati, A; Marchetti, C; DeFelice, F; Tranquillo, V; Iacobelli, V; Quagliozzi, L; Salutari, V; Scambia, G; Fagotti, A
Abstract : Introduction: Neoadjuvant chemotherapy (NACT) and subsequent interval debulking surgery (IDS) has been proposed as an alternative to primary debulking surgery in advanced epithelial ovarian carcinoma. However, no biomarkers of NACT efficacy are reliable in predicting chemo response. This study aimed to identify pre-operative factors of IDS success probability. Methods: Single institution, retrospective study. Preoperative variables were used to predict the likelihood of IDS using multivariable models. A nomogram was developed and internal validation was performed. Results: 359 women were submitted to NACT between January 2016 and June 2019. A complete cytoreductive surgery was achieved in 255 (85%) patients, while an optimal/suboptimal cytoreduction was reached in the remaining 46 (15%) and 58 (16%) did not undergo surgery after NACT. Women with BRCA 1/2 mutation (OR 4.84, CI 95% 1.75—13.34; p= 0.002) and lower tumour load (OR 8.15, CI 95%1.06–62.32; p= 0.043) were more likely to undergo IDS. Among patients who did not undergo IDS, only 5 (13%) presented with BRCA 1/2 mutation, compared with 34 (87%) wild type BRCA (p<0.001). According to the predictive model, we constructed a nomogram to report the probability of IDS using five variables: age, Charlson-comorbidity category, histology, LPS-PIV and BRCA-status (figure 1 ). The calibration plot demonstrated good agreement between predicted and actual probability of surgical treatment (figure 2 ). Conclusions: This is the first nomogram developed in this setting and it might help physicians with their decision-making algorithm.